The Study of Corrosion Behaviour of Cobalt-Iron (CoFe) Alloy Coating / Nor Fazli Adull Manan ...[et al.] - Adull Manan, Nor Fazli; Nik Mohd Masdek, Nik Rozlin; Abdul Aziz, Qayyum; Salleh, Zuraidah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Cobalt-Iron (CoFe) nanocrystalline alloy coating were successfully electrodeposited in a sulfate bath by supplying direct current to the 304-stainless steel and AISI 1080 mild steel substrates. The objective of this research is to study the corrosion behaviour of deposited CoFe coating on the substrates by the characterization test and the corrosion rate test. The electrodeposition method was done by controlling the operating parameter such as temperature, pH, current, deposition time and sulfate bath composition. The bath temperature was maintained at 40 ◦C for 30 minutes with an acidic condition of pH 3.5. The iron content was varied at 1.39 g, 2.76 g, and 5.56 g to study its influence on the physical properties such as size of nanoparticles, phase and crystallographic structure, surface roughness and microhardness of CoFe coatings. The CoFe nanocrystalline of 1018 mild steel with 2.76 g Fe content achieved the highest average microhardness of 324.32 HV compared to 304 stainless steel. The experimental result from X-Ray Diffraction (XRD) test shows that the particles sizes of CoFe alloy coating decreases with an increase of Fe content. Furthermore, it was found that the highest surface roughness recorded is 9.86 μm for 2.76 g of Fe content. Also, a potentiodynamic polarization test (PDP) method was used to assess the corrosion performance of the coating on each substrate material. At the end of the research, the corrosion resistance of the CoFe alloy on 304 stainless steel substrate has better corrosion resistance than AISI 1018 mild steel.